Analysis of nurse's ability in preventing nosocomial infections on floor 6B using the Nvivo method at RSU Royal Prima Medan 2022 - Deborah Angelin Purba; Chrismis Novalinda Ginting; Sri Wahyuni (Priviet Social Sciences Journal, 2023)
Nosocomial infection is an infection originating from a hospital caused by hospital staff or health workers during the health service process or hospital visitors. The background of this research is the lack of role of nurses in the process of preventing nosocomial infections. The purpose of this study was to explain the role of nurses in preventing nosocomial infections at RSU Royal Prima. This type of research uses a qualitative approach with in-depth interviews with informants so that they can clearly and in-depth know the role of nurses in preventing nosocomial infections at RSU Royal Prima. The results showed that nurses already know how to report to a doctor if there are signs and symptoms of infection and transmission of infectious diseases and protect against precautions while on duty at the hospital. However, there are still nurses who do not know optimally in terms of maintaining hospital cleanliness. In maintaining hand hygiene, nurses only know in terms of hand washing, the implementation is not in accordance with the procedure. In using Personal Protective Equipment, nurses know their role in terms of wearing masks and gloves, but in practice there are still nurses who have not used Personal Protective Equipment according to standards. In addition, there are obstacles for nurses in preventing nosocomial infections such as inadequate infrastructure.